2011
DOI: 10.1128/aem.02983-10
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Obligate Intracellular Bacterium in the Midgut Epithelium of the Bulrush Bug Chilacis typhae (Heteroptera, Lygaeidae, Artheneinae)

Abstract: Many members of the suborder Heteroptera have symbiotic bacteria, which are usually found extracellularly in specific sacs or tubular outgrowths of the midgut or intracellularly in mycetomes. In this study, we describe the second molecular characterization of a symbiotic bacterium in a monophagous, seed-sucking stink bug of the family Lygaeidae (sensu stricto). Chilacis typhae possesses at the end of the first section of the midgut a structure which is composed of circularly arranged, strongly enlarged midgut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 53 publications
3
62
0
Order By: Relevance
“…Buchner, 1965;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2012Kuechler et al, , 2013Swiatoniowska et al, 2013 for further details). Both the histological studies of Buchner (1965Buchner ( , 1966Buchner ( , 1967) and more recent ultrastructural studies (Cheng & Hou, 2001;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2011Kuechler et al, , 2012Koga et al, 2012;Matsuura et al, 2012;Swiatoniowska et al, 2013) have revealed that the latter transmission of endosymbionts (termed transovarial transmission) may differ even in closely related groups of hemipterans. The endosymbiotic microorganisms may invade young germ cells termed cystocytes (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buchner, 1965;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2012Kuechler et al, , 2013Swiatoniowska et al, 2013 for further details). Both the histological studies of Buchner (1965Buchner ( , 1966Buchner ( , 1967) and more recent ultrastructural studies (Cheng & Hou, 2001;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2011Kuechler et al, , 2012Koga et al, 2012;Matsuura et al, 2012;Swiatoniowska et al, 2013) have revealed that the latter transmission of endosymbionts (termed transovarial transmission) may differ even in closely related groups of hemipterans. The endosymbiotic microorganisms may invade young germ cells termed cystocytes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive, histological investigations by Buchner (1965) and more recent ultrastructural studies (Cheng & Hou, 2001;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2010Kuechler et al, , 2011Matsuura et al, 2012;Swiatoniowska et al, 2013) have shown that during hemipteran evolution various modes of inheritance of endosymbiotic microorganisms by subsequent generations have developed. The extracellular gut bacteria that are typical of most the heteropterans so far examined (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Schneideria nysicola" but is phylogenetically close to "Ca. Rohrkolberia cinguli," the endosymbiont of Chilacis typhae (Artheneidae), which is harbored in enlarged epithelial cells of the midgut (28).…”
Section: Discussionmentioning
confidence: 99%
“…and Nysius spp. : a "bacteriocytic belt" exists at the anterior end of the midgut, which consists of circularly arranged, strongly enlarged midgut epithelial cells whose cytoplasm is full of a specific endosymbiont belonging to the Gammaproteobacteria (28). In all these cases, the endosymbionts are vertically transmitted via transovarial passages, which is typical of intracellular symbiotic associations (35).…”
mentioning
confidence: 99%
See 1 more Smart Citation